(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
As a result of mycological research 290 species of fungi from various systematic groups belonging to the Ascomycota and Basidiomycota were recorded on the territory of the Male Polissia National Nature Park. The powdery mildews and discomycetes (55 and 15 species, respectively) dominated among the recorded Ascomycota. The agaricoid (120 species), aphyllophoroid (36 species), boletoid (19 species) and the rust fungi (9 species) prevailed among Basidiomycota. Of the identified species, 289 are first noted for the park, 56 species are new for Central Polissia; 42 species are new for Polissia; eight species (Clitocybe sinopica, Conocybe ambiqua, Cortinarius decipiens, Entoloma graphitipes, Galerina hybrida, Lactarius scoticus, Russula aquosa and R. betularum) and one variety (Cortinarius flexipes var. flabellus) were first recorded for Ukraine. New localities of the two species listed in the Red Data Book of Ukraine, i.e. Grifola frondosa and Pseudoboletus parasiticus were noted within the park. Some macromycetes, which are rare or relatively rare in Ukraine, are also found (Amylocorticium canadense, Conocybe subxerophytica var. brunnea, Cortinarius diasemospermus, C. flexipes var. flexipes, Entoloma rhodocalix, Flammulaster muricatus, Galerina atkinsoniana, G. norvegica, Lachnella alboviolascens, Melanoleuca microcephala, Mycena niveipes, and M. viridimarginata). Among the powdery mildews Erysiphe lycopsidis, E. mayorii, E. penicillata, E. urticae, Golovinomyces circumfusus, Phyllactinia alnicola, Podosphaera epilobii, P. major and P. myrtillina are relatively rare. The record of the rust fungus Kuehneola uredinis is the easternmost in Ukraine. The relatively rare discomycetes comprise Ascobolus carbonarius, Coccomyces tumidus, Leotia lubrica, Mollisia olivascens, and Scutellinia crinita. Some rare species have also been found among the fungicolous fungi, such as Fusicolla merismoides, Hypomyces luteovirens and Tomentella ellisii. The work contains a list of all species of fungi recorded in the Male Polissia National Nature Park during this study.